Analysis Of The Dynamics Of Cashless Payments In Kazakhstan In The Context Of The Covid-19 Pandemic - A. Kredina; A. Akparova; L. Vasa (Экономика: стратегия и практика)
The COVID-19 pandemic has accelerated the development of FinTech and the transition to cashless payments of the population of various countries, including Kazakhstan. For provision of cashless payments there are created platforms which work in NFC & MFS systems, they protected by security protocols (Secure Element (SE)) and allow to store confidential user data. Changes in the business model of banks have led to the emergence of a new format of banking products and services that can be used through smartphones (the main operating systems Android and iOS). The goal of the study is to analyze the dynamics of the impact of the COVID-19 pandemic on the use of cashless payments through national payment systems in Kazakhstan. Based on the goal, a null and an alternative hypothesis were set, of which the second was confirmed in the result. Research methods used to write this article are economic and statistical analysis and synthesis, graphical method, analysis of the series of dynamics. The data for the study was taken from the NBK Statistical Bulletin: data on cashless payments through the Interbank System of Money Transfer (ISMT) and the Interbank Clearing System (ICS) for the period from 2002 to 2020. The impact of the COVID-19 pandemic on the dynamics of the transformation of cashless payments made by using financial technologies has been proved. Recommendations for further improvement of the financial system are given. The development of national payment systems makes it possible to reduce the level of fraud in the financial sector, to increase the speed of cashless transfers and level out transaction errors. Study limitation: only national payment systems ISMT and ICS were used.